Current Practices in Choosing Estimands and Sensitivity Analyses in Clinical Trials: Results of the ICH E9 Survey. (January 2017) - Fletcher, C.; Tsuchiya, S.; Mehrotra, D.V.
Background: An addendum to the International Conference on Harmonisation E9 (ICH E9) guidance document (Statistical Principles for Clinical Trials) is currently under development. The aim of the addendum is to promote harmonized standards on the choice of estimand (a well-defined measure of the treatment effect that is being estimated) in clinical trials and to describe a consensual framework for planning, conducting, and interpreting sensitivity analyses of clinical trial data. Methods: In order to help understand current practices relating to the choice of estimands and sensitivity analyses for clinical trials, the ICH E9 working group developing the addendum conducted a survey with a primary focus on clinical trials involving drugs, vaccines, and biologics. The survey was distributed electronically between May 19, 2015, and June 11, 2015, to various stakeholder groups within ICH, including industry, regulatory, and academic communities. A total of 1305 respondents participated. Results: Of the 1305 respondents 547 (42%), 344 (26%) and 283 (22%) were from Europe, USA and Japan respectively. Over half of the respondents work in pharmaceutical companies, and approximately a quarter of respondents noted oncology as the primary therapeutic area they work in. Over half of the respondents (595, 55%) noted the treatment effect being estimated was 'in the entire target population of patients regardless of whether they will take treatment as instructed'. The most common methods for handling missing data in primary analyses were mixed-models repeated measures (555, 56% respondents) and last observation carried forward (549, 55% respondents). The majority of respondents (816, 83%) noted they conducted sensitivity analyses to estimate treatment effects in different ways compared to the primary analysis by using alternative assumptions (627, 78%) and/or using alternative statistical methods (616, 76%). Conclusions: The survey results have provided useful information to the ICH E9 working group on current practices on the choice of primary estimands for measuring treatment effects in confirmatory clinical trials, and approaches used to select sensitivity analyses.